Dapagliflozin utilization following hospitalization for heart failure: real-world insights from EVOLUTION HF, a multinational, observational study. (3rd October 2022) - Savarese, G; Bozkurt, B; Adamsson Eryd, S; Bodegard, J; Lund, L H; Thuresson, M; Vardeny, O; Kishi, T
Abstract: Background: Use of guideline-directed medical therapies (GDMTs) in patients with heart failure (HF) with reduced ejection fraction (HFrEF) – such as renin–angiotensin–aldosterone system inhibitors, beta-blockers, mineralocorticoid receptor antagonists and angiotensin receptor neprilysin inhibitors – is suboptimal, especially after hospitalization for HF (hHF). Dapagliflozin was the first sodium–glucose co-transporter-2 inhibitor approved in patients with HFrEF. In the DAPA-HF study, dapagliflozin decreased the risk of hHF and mortality in patients with HFrEF (with or without type 2 diabetes) compared with placebo. Little is known about the real-world characteristics and treatment profiles of patients initiating dapagliflozin after hHF in clinical practice. Purpose: EVOLUTION HF aims to describe characteristics and real-world treatment patterns in patients who initiated GDMTs following hHF. Using data available to date, we focused on dapagliflozin use in two countries (Japan and Sweden). Methods: EVOLUTION HF is a multinational observational, longitudinal cohort study using claims and electronic health record databases, which included 514, 869 patients with hHF during the study period. Adult patients who initiated dapagliflozin between December 2020 and September 2021 (Japan) or December 2021 (Sweden) were identified and included if they initiated dapagliflozin 10 mg once daily during hHF or within 12 months after a hHF discharge. Patient characteristics and treatment profile at index (initiation of dapagliflozin) are reported overall and by country. Results: Overall, 7023 patients were included (3515 from Japan, 3508 from Sweden; Table 1); the mean age was 73±13 years and 70% were male. The median lengths of the hHF leading to dapagliflozin initiation were 16 (interquartile range [IQR] 9–26) days in Japan and 4 (IQR 2–7) days in Sweden. Overall prevalences of atrial fibrillation, chronic kidney disease, diabetes and established cardiovascular disease were 50%, 23%, 34% and 57%, respectively. Of the 7023 patients who initiated dapagliflozin during hHF or within 12 months of hHF discharge, 45%, 62%, 75% and 87% of patients initiated dapagliflozin in hospital/within 7 days of discharge or within 1, 3 or 6 months of discharge, respectively. Japan had a higher proportion of patients who initiated dapagliflozin in hospital/within 7 days of hHF discharge compared with Sweden (64% vs 27%; Figure 1). At dapagliflozin initiation, 37% and 74% of patients in Japan and Sweden, respectively, had three or four other GDMTs. Conclusions: Patients who initiated dapagliflozin following hHF often had comorbidities associated with increased risk of adverse cardiorenal outcomes. Timing of dapagliflozin initiation and use of other GDMTs at index varied between countries. A large proportion of patients initiated dapagliflozin more than 1 month after a hHF or in addition to three or four other GDMTs, indicating an opportunity for earlier dapagliflozin use in patients with HF. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): AstraZeneca